Brand Integration Practices in Mergers and Acquisitions - Vũ, Anh Dũng (2016)
This paper aims to capture and systematise those practices which have been proven as good skills, tactics, methods, and techniques at effectively and efficiently delivering particular outcomes behind brand integration in various mergers and acquisitions (M&As). These practices can be shared and learned to increase the probability of brand integration success in future M&As. The paper adopts the case-study method by interviewing several top-level executives, M&A managers, functional managers and members of M&A projects which have been involved in M&As. Twenty practices are outlined and defined after analysing ten M&A events within six case companies (which are multinational corporations – MNCs). The paper provides managers with insights into good (or winning) practices that MNCs have adopted in integrating brands in their M&As by addressing a number of specific issues and corresponding solutions. The twenty practices for the integration of brands in M&As are classified into eight major clusters according to the dimensions of brand and brand management these practices are related to – brand strategic positioning, brand people, brand knowledge transfer, brand integration planning, brand integration implementation, brand disposal expertise, brand disposal negotiation, and brand due diligence. These clusters allow M&A and integration managers to accumulate their own brand integration practices from time to time systematically. These also help facilitate the adoption of a learning approach by firms to their later M&As